Desarrollo de un modelo de estandarización operacional para el diseño de sartas selectivas en pozos inyectores del campo la Cira Infantas (2018)
In this project the standardization of parameters and variables that directly affect the design of selective injection strings in the La Cira Infantas Field was carried out, in order to guarantee that the designs which will be run in the future in injection wells of the LCI Field be done safely, optimal and efficient way, to achieve the objective, we had the support of the company company Occidental de Colombia LLC. In the first place, the compilation of the information necessary to develop the research work was carried out; taking into account the design procedures of selective strings used by the company, a historical study was made, which allowed defining the variables and operational parameters that are applied when a string desing is generated, then a statistical analysis was developed of each injector well history and its cause of failure, the analysis was developed with a significant sample of injectors wells of Campo la Cira Infantas, with this analysis and the collaboration of companies related to the activity of Occidental de Colombia LLC responsible for providing the tools for the design of the selective injection strings, an optimal range of operation for each of the parameters and variables under study was determined.